Benefit of Practice of the Stroop Test in Young and Older Adults: Pattern of Gain and Impact of Educational Level. - Burger, Lucile; Fay, Séverine; Angel, Lucie; Borella, Erika; Noiret, Nicolas; Plusquellec, Pierrich; Taconnat, Laurence (Experimental Aging Research)
Back-Ground/Study Context: The goal of this study was to examine how repeated practice of an inhibition test could improve performance in the test in young and older adults. In particular, we wished to explore whether the gains made during a practice program varied between age groups, and how educational level influenced practice-related gains in older adults. Thus, we tried to disentangle two hypotheses explaining the benefits of practice, namely compensation (greater gain by the lowest performers) and magnification (greater gain by the highest performers). Method: Thirty-three younger adults and 60 older adults were divided into two groups each: (1) Groups in the Practice condition had 10 sessions practicing different versions of Card C of the Stroop Test, (2) groups in the Control condition completed only the pretest and posttest. Results: Overall, results showed that the performance of both young and older adults improved more in the practice condition than in the control condition. The older adults benefited more from practice than the young adults, with earlier and more regular improvement over the 10 sessions. Moreover, the older adults with a higher educational level benefited most. Discussion: These findings seem to support both the compensation and the magnification hypotheses, depending on the variable (age or educational level).